Biofilm production and resistance profile of Enterobacter sp. strains isolated from pressure ulcers in Petrolina, Pernambuco, Brazil - Gleise G. Soares; Joice F. Costa; Flávia B. S. Melo; Rachel Mola; Tereza Cristina L. Balbino
ABSTRACT Introduction: The Enterobacter genus is formed by lactose-fermenting bacteria. These microorganisms cause a wide range of hospital infections such as pneumonia, urinary tract infections and wounds; and they are associated with the colonization of medical devices. Objective: To define the resistance profile and the biofilm production of Enterobacter sp. strains isolated from pressure ulcers. Materials and methods: A quantitative field research (documentary) type laboratory study performed at a hospital in the municipality of Petrolina (PE). Samples were collected from 30 wounds of internal medicine inpatients with stage II pressure ulcers, using the Z-technique with sterile swabs, from February to May 2014. Results: The most prevalent bacteria were Enterobacter sp. and Escherichia coli. All proved multiresistant to antibiotics. Most strains of Enterobacter sp. were classified as moderate biofilm producer. Conclusion: The strains of Enterobacter sp. showed high resistance to the antimicrobials used in clinical routine.